Pembentukan kemandirian melalui pembelajaran kewirausahaan sosial untuk meningkatkan kesadaran sosial dan kesadaran ekonomi - Endah Andayani; Lilik Sri Hariani; Muchammad Jauhari (Jurnal Riset Pendidikan Ekonomi, 2021)
The establishment of self-reliance through social entrepreneurship learning to increase students' socioeconomic awareness is an important issue, especially in formal educational institutions that are vulnerable from global influence, in the direction of policy and strategic direction of the Directorate of Vocational Education development focuses on motivating schools to progress, regrow discipline and responsibility, mental development and noble morals of vocational school students, and the creation of a resilient and independent young generation. This study aims to describe in detail how the establishment of self-reliance through social entrepreneurship activities can increase the socioeconomic awareness of the students and why this should be done. In accordance with the characteristics of vocational school students, who are required to have work-ready competencies and even able to create a world of work for others so as to provide socioeconomic changes, as well as re-encourage social entrepreneurship activities to help create self-reliance on socioeconomic activities faced in society. This research uses qualitative approach with retrospective case study model at SMK Islam Terpadu Asy-Ayadzili Pakis Malang Regency and conducted during the ongoing incident. This research method is intended to obtain a model or social engineering about the process of establishing proper independence through social entrepreneurship and the reason for the need for self-reliance. The results found that the establishment of self-reliance through social entrepreneurship to improve social and economic welfare is a very strong reason implemented social entrepreneurship. Constraints in developing entrepreneurial values in students are low student confidence, limited time sharing with pesantren activities, strict rules and schedules in the cottage, lack of cooperation between students, difficulty finding the right business.